Polymer matrix containing mesogenic ligands and optical shutter containing same - Patents.com
By integrating mesogen ligand nanoparticle complexes into the polymer matrix of PDLC devices, the issue of high driving voltages due to impurity ions is addressed, resulting in improved performance and efficiency by enhancing dispersibility and capturing impurity ions.
Patent Information
- Application Number
- JP2024555154
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-29
- Filing Date
- 2023-03-24
- Publication Date
- 2025-04-30
AI Technical Summary
Existing polymer dispersed liquid crystal (PDLC) devices require high driving voltages due to impurity ions present in the liquid crystal material, which reduces their performance and efficiency.
Incorporating mesogen ligand nanoparticle complexes into the liquid crystal composition to improve dispersibility and capture impurity ions, thereby reducing the driving voltage required for the PDLC device.
The use of mesogen ligand nanoparticle complexes in the polymer matrix of PDLC devices effectively lowers the driving voltage and enhances the performance and efficiency of the devices by improving the dispersibility of inorganic particles and capturing impurity ions.
Smart Images

Figure 2025513706000001_ABST
Abstract
Description
[Technical field]
[0001] [CROSS REFERENCE TO RELATED APPLICATIONS] This application claims priority to U.S. Provisional Patent Application No. 63 / 325,089, filed March 29, 2022, which is incorporated by reference in its entirety.
[0002] The present disclosure relates to a polymer matrix containing liquid crystal compounds doped with inorganic nanoparticles having mesogenic ligands on the surface to improve dispersibility, and further relates to a light shutter containing the polymer matrix to reduce the driving voltage in an emulsified polymer dispersed liquid crystal (PDLC). [Background technology]
[0003] In the fenestration industry, smart windows are an attractive alternative to traditional mechanical shutters, blinds or hydraulic shading methods. Efforts have been made to optimize smart windows to control the light waves that pass through them, such as ultraviolet, visible and infrared light. Such control can provide privacy, reduce heat from ambient sunlight and control the harmful effects of ultraviolet light. Currently, polymer dispersed liquid crystal (PDLC) is a prominent technology that is often used for smart window applications.
[0004] PDLC light shutters involve phase separation of nematic liquid crystals from a homogeneous mixture of liquid crystal and polymer disposed between two parallel substrates with transparent electrodes. The phase separated nematic liquid crystals form microdomains / microdroplets dispersed within a polymer matrix. In the OFF state, the liquid crystals contained in these microdroplets are randomly oriented, resulting in a refractive index mismatch between the polymer matrix and the liquid crystal, resulting in an opaque (light scattering state). Application of an external electric field to the light shutter causes the liquid crystals to orient to match the refractive index between the polymer matrix and the liquid crystal, resulting in a transparent state.
[0005] Disadvantages of PDLC include the need for large continuous voltages due to impurity ions that are often present in liquid crystal-based devices, which reduces performance and efficiency. The presence of impurity ions in PDLC can alter the performance and efficiency of such liquid crystal devices. These undesirable impurities are present even if the liquid crystal material is very thoroughly purified before use.
[0006] There is therefore a need to reduce the power consumed by liquid crystal devices by lowering the driving voltage and / or reducing the deleterious effects of impurity ions present in the liquid crystal material and in the liquid crystal device. Summary of the Invention
[0007] A novel approach to address the presented problem involves the addition of mesogenic ligand nanoparticle conjugates to the liquid crystal composition to achieve improved dispersibility in the liquid crystal compound, resulting in a lower drive voltage for the PDLC device.The present disclosure describes an optical shutter comprising a first base element comprising a transparent electrode layer, a second base element comprising a transparent electrode layer, and a polymer matrix disposed between and in electrical communication with the first and second base elements.
[0008] Some embodiments include a polymer matrix, hi some embodiments, the polymer matrix includes at least one mesogenic ligand nanoparticle conjugate and at least one liquid crystal compound.
[0009] In some embodiments, the mesogenic ligand nanoparticle conjugate comprises an alkylamine ligand or an arylamine ligand. In some embodiments, the mesogenic ligand nanoparticle conjugate comprises a precious metal nanoparticle. In some embodiments, the precious metal nanoparticle comprises gold nanoparticles. In some embodiments, the mesogenic ligand nanoparticle conjugate may comprise a semiconducting material. In some embodiments, the semiconducting material comprises indium tin oxide.
[0010] In some embodiments, the concentration of the mesogenic ligand nanoparticle conjugate is about 0.01% to about 5% by weight of the total weight of the polymer matrix. In some embodiments, the polymer matrix may further comprise an alkylamine spacer or an alkylthiol spacer. In some embodiments, the ratio of the alkylamine spacer to the mesogenic ligand nanoparticle conjugate or the ratio of the alkylthiol spacer to the mesogenic ligand nanoparticle conjugate may be about 2:1 to about 1:2.
[0011] In some embodiments, the at least one liquid crystal compound may comprise a polymer dispersed liquid crystal. In some embodiments, the at least one liquid crystal compound comprises an emulsified polymer dispersed liquid crystal.
[0012] In some embodiments, at least one liquid crystal compound may include a resin.
[0013] These and other embodiments are described in more detail below. [Brief description of the drawings]
[0014] [Figure 1] 1A-1C are cross-sectional views of possible embodiments of the optical shutter. [Diagram 2] 1 is an image showing the dispersibility of an embodiment of a mesogenic ligand. [Diagram 3] 1 is an image showing the dispersibility of an embodiment of a mesogenic ligand. [Figure 4] 1 is an image showing the dispersibility of an embodiment of a mesogenic ligand. [Diagram 5] 11 is a graph illustrating the performance of an embodiment of the optical shutter. [Figure 6] 11 is a graph illustrating the performance of an embodiment of the optical shutter. [Figure 7] 11 is a graph illustrating the performance of an embodiment of the optical shutter. [Figure 8] 11 is a graph illustrating the performance of an embodiment of the optical shutter. [Figure 9] 11 is a graph illustrating the performance of an embodiment of the optical shutter. [Figure 10] 11 is a graph illustrating the performance of an embodiment of the optical shutter. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Some embodiments of the present disclosure include light shutters that include a polymer matrix, which can be used in window-type applications for energy efficiency and privacy. The polymer matrix of the present disclosure may include at least one mesogenic ligand nanoparticle conjugate and at least one liquid crystal compound. The present disclosure includes mesogenic ligand nanoparticle conjugates that act to reduce the driving voltage in the light shutter by improving the dispersibility of inorganic particles and the capture of impurity ions present in the liquid crystal medium. Thus, the light shutters of the present disclosure are energy-saving. The present disclosure also describes light shutters that allow switching between an opaque light-scattering state and a transparent state by application of an electromagnetic field.
[0016] As used herein, the term "transparent" refers to a structure that does not absorb or reflect significant amounts of visible light, but rather is transmissive to visible light.
[0017] The term "about" as used herein can include any numerical value that can vary without changing the basic function of its value. When used in conjunction with a range, "about" also discloses a range defined by the absolute values of the two endpoints. The term "about" can refer to plus or minus 10% of the stated number.
[0018] The term "polymer matrix" is a term of art and as used herein refers to a viscous composition or mixture of at least one mesogenic ligand nanoparticle conjugate and at least one liquid crystal compound. The matrix may contain solvents, crosslinkers and other polymerizable monomers.
[0019] As used herein, the term "mesogenic ligand nanoparticle conjugate" refers to a nanoparticle having a mesogenic ligand attached at its surface by a covalent bond.
[0020] The present disclosure includes an optical shutter comprising a pair of opposing transparent electrodes. In some embodiments, the opposing transparent electrodes can define an electrode surface. Some embodiments include an optical shutter, which can include a polymer matrix. In some embodiments, the polymer matrix can be disposed between the transparent electrodes, e.g., sandwiched between the transparent electrodes. In some embodiments, the polymer matrix can be in electrical communication with the transparent electrodes. In some embodiments, the polymer matrix can include at least one mesogenic ligand nanoparticle composition. In some embodiments, the polymer matrix can include at least one liquid crystal compound. In some embodiments, the at least one liquid crystal compound has a structure in which the liquid crystal is phase-separated in the polymer matrix.
[0021] Some of the components of the optical shutter of the present disclosure are described in US Patent Application Publication No. 2022 / 0035197, which is incorporated herein by reference in its entirety. An exemplary first embodiment of the optical shutter of the present disclosure is shown in FIG. 1. The optical shutter, e.g., optical shutter 100, generally comprises a first base element, e.g., first base element 10, with a transparent electrode layer, a second base element, e.g., second base element 20, with a transparent electrode layer, and a polymer matrix, e.g., polymer matrix 30, sandwiched between base element 10 and base element 20 with a transparent electrode layer and in electrical communication with a pair of opposing transparent electrodes.
[0022] In some embodiments, the first base element 10 with the transparent electrode layer comprises a first transparent substrate, e.g., a transparent substrate 12, a first transparent electrode layer, e.g., a transparent electrode layer 14, disposed on one side thereof, and a first hard coat layer, e.g., layer 16, disposed on the opposite side of the transparent substrate with respect to the polymer matrix 30. The first base element 10 with the transparent electrode layer may comprise a second hard coat layer (not shown) between the first transparent substrate 12 and the first transparent electrode layer 14 instead of or in addition to the first hard coat layer 16. In some embodiments, the first base element 10 with the first transparent electrode layer 14 may not comprise both the first hard coat layer 16 and the second hard coat layer. In some examples, the first base element 10 with the first transparent electrode layer 14 preferably comprises the first hard coat layer 16, more preferably both the first hard coat layer 16 and the second hard coat layer. In some embodiments, although not shown, an alignment film may be disposed on the surface of the transparent electrode layer depending on the driving mode.
[0023] The first transparent electrode layer 14 may include a metal oxide. The metal oxide may include, but is not limited to, indium tin oxide (ITO), zinc oxide (ZnO), and tin oxide (SnO2). In some embodiments, the metal oxide may be an amorphous metal oxide or a crystalline metal oxide. In other embodiments, the first transparent electrode layer 14 may be formed of a metal nanowire such as a silver nanowire (AgNW), a carbon nanotube (CNT), an organic conductive film, a metal layer, or a laminate thereof. In some embodiments, the first transparent electrode layer 14 may be patterned into a desired shape depending on the intended purpose.
[0024] The first transparent electrode layer 14 may preferably have a thickness of about 0.01 μm to about 0.1 μm, about 0.01 μm to 0.045 μm, about 0.01 μm to 0.02 μm, about 0.02 μm to 0.03 μm, about 0.03 μm to 0.04 μm, about 0.04 μm to 0.05 μm, about 0.05 μm to 0.06 μm, about 0.06 μm to 0.07 μm, about 0.07 μm to 0.08 μm, about 0.08 μm to 0.09 μm, about 0.09 μm to 0.1 μm, or any thickness within a range determined by any of these values.
[0025] The first transparent substrate 12 is not particularly limited, and any suitable transparent substrate can be used. In some embodiments, the first transparent substrate 12 includes, but is not limited to, a glass substrate, a polymer substrate, or a polyethylene terephthalate (PET) substrate.
[0026] In some embodiments, when the transparent substrate 12 is composed of a polymer substrate, a polymer film containing a thermoplastic resin as a main component is typically used. Some non-limiting examples of thermoplastic resins include, but are not limited to, cycloolefin-based resins, such as polynorbornene; acrylic resins; polyester-based resins; polycarbonate resins; and cellulose-based resins. In some embodiments, cycloolefin-based resins or acrylic resins may be preferably used. Each of these resin films is relatively brittle and flexible, so that the film may easily break when folded. In some embodiments, the thermoplastic resins may be used alone or in combination.
[0027] The first transparent substrate 12 preferably has a thickness of about 20 μm to about 200 μm, about 30 μm to 100 μm, about 20 μm to 40 μm, about 40 μm to 60 μm, about 60 μm to 80 μm, about 80 μm to 100 μm, about 100 μm to 120 μm, about 120 μm to 140 μm, about 140 μm to 160 μm, about 160 μm to 180 μm, about 180 μm to 200 μm, or any thickness within a range defined by any of these values.
[0028] The first hard coat layer 16 and the second hard coat layer may provide the optical shutter 100 with scratch resistance and surface smoothness. In some embodiments, the hard coat layer 16 is composed of a cured layer of any suitable UV-curable resin. Non-limiting examples of the UV-curable resin include acrylic resin, silicone-based resin, polyester-based resin, urethane-based resin, amide-based resin, epoxy-based resin, or a combination thereof. In some examples, the hard coat layer may be formed by applying a coating solution containing a monomer or oligomer of such a UV-curable resin and a photopolymerization initiator to the first transparent substrate 12, drying the coating solution, and irradiating the dried coating layer with UV light to cure the coating layer.
[0029] The hard coat layer has a thickness of preferably 0.4 μm to 40 μm, more preferably 1 μm to 10 μm. In one embodiment, the thickness of the hard coat layer (total thickness when the first hard coat layer and the second hard coat layer are formed) can be set to 1% to 20%, preferably 2% to 15% of the thickness of the first transparent substrate 12.
[0030] The haze value of the first base element 10 having the transparent electrode layer is preferably about 20% or less, more preferably about 10% or less, or even more preferably about 0.1% to 10%. The total light transmittance of the first base element 10 having the transparent electrode layer is preferably about 30% or more, more preferably about 60% or more, or even more preferably about 80% or more.
[0031] In some embodiments, the second base element 20 with the transparent electrode layer comprises a second transparent substrate, e.g., a transparent substrate 22, a second transparent electrode layer, e.g., a transparent electrode layer 24, disposed on one side thereof, and a third hard coat layer, e.g., layer 26, disposed on the opposite side of the transparent substrate. The second base element 20 with the transparent electrode layer may comprise a fourth hard coat layer (not shown) between the second transparent substrate 22 and the second transparent electrode layer 24 instead of or in addition to the third hard coat layer 26. In some embodiments, the second base element 20 with the second transparent electrode layer 24 may not comprise both the third hard coat layer 26 and the fourth hard coat layer. In some examples, the second base element 20 with the second transparent electrode layer 24 preferably comprises the third hard coat layer 26, more preferably both the third hard coat layer 26 and the fourth hard coat layer. In some embodiments, although not shown, an alignment film may be disposed on the surface of the transparent electrode layer depending on the driving mode.
[0032] The haze value of the second base element 20 having a transparent electrode layer is preferably about 20% or less, more preferably about 10% or less, and even more preferably about 0.1% to about 10%. The total light transmittance of the second base element 20 having a transparent electrode layer is preferably about 30% or more, more preferably about 60% or more, or even more preferably about 80% or more.
[0033] The same statements detailed above for the first transparent electrode layer 14, the first transparent substrate 12, the first hardcoat layer 16, and the second hardcoat layer may also apply to the second transparent electrode layer 24, the second transparent substrate 22, the third hardcoat layer 26, and the fourth hardcoat layer, respectively. The second base element 20 with the transparent electrode layer may be of the same construction as the first base element 10 with the transparent electrode layer, or may be of a different construction.
[0034] In some embodiments, the light shutter 100 comprises a polymer matrix 30. In some embodiments, the polymer matrix 30 comprises at least one mesogenic ligand nanoparticle conjugate and at least one liquid crystal compound.
[0035] In some embodiments, the mesogenic ligand of the mesogenic ligand nanoparticle conjugate may comprise an alkylamine ligand and / or an arylamine ligand. In some embodiments, the mesogenic ligand may comprise a substituted aryl group. In some embodiments, the substituted aryl group may comprise an amino functional group. In some embodiments, the substituted aryl group may comprise a C2-C 12 In some embodiments, the substituted aryl group may be a substituted 1,1'-biphenyl]-4-carbonitrile. In some embodiments, the substituted 1,1'-biphenyl]-4-carbonitrile has the formula: [ka] (Wherein, R1 is [ka] , -H, or -F; m can be 2 to 4 (e.g., two aryl groups); X can be -O- or -S-; n can be from about 5 to about 15 (e.g., 10); and R2 can be -COOH, -C=CH2, -OH, -SH, -NH2, -N3, or any functional group suitable for facilitating covalent bonding with each selected nanoparticle as described below).
[0036] In another embodiment, the mesogenic ligand of the mesogenic ligand nanoparticle conjugate has the formula: [ka] where X can be -O- or -S-, n can be from about 5 to about 15 (e.g., 10), and R is independently selected from -COOH, -C=CH2, -OH, -SH, -NH2, and / or -N3. In some embodiments, the mesogenic ligand nanoparticles may have: [ka] where n and X are as defined above, or any combination thereof.
[0037] In some embodiments, the mesogenic ligand of the mesogenic ligand nanoparticle conjugate may comprise a substituted aryl group or a substituted cyclohexyl group. In some embodiments, the substituted aryl group may be a substituted 1,1'-biphenyl. In some embodiments, the mesogenic ligand nanoparticle conjugate may comprise [ka] where R3 may include -COOH, -C=CH2, -OH, -SH, -NH2, -N3, or any functional group suitable for facilitating covalent bonding with each selected nanoparticle, or any combination thereof.
[0038] In some embodiments, the polymer matrix 30 may include a plurality of spacers. In some embodiments, the polymer matrix 30 may include an alkylamine spacer. In some embodiments, the alkylamine spacer is a C3 to C6 alkylamine spacer. 12 Alkylamines, such as hexylamine ( [ka] In some embodiments, the carbon chain length of the alkylamine spacer can be 3, 4, 5, 6, 7, 8, 9, 10, 11, or 12 carbon atoms.
[0039] In some embodiments, the polymer matrix 30 may include an alkylthiol spacer. In some embodiments, the alkylthiol spacer is a C3-C 12 Alkylthiols, such as hexanethiol ( [ka] In some embodiments, the carbon chain length of the alkylthiol spacer can be 3, 4, 5, 6, 7, 8, 9, 10, 11, or 12 carbon atoms.
[0040] In some embodiments, the length of the spacer can be selected to improve the dispersity of the mesogenic ligand nanoparticle conjugate in the liquid crystal compound. The length of the spacer can be selected based on the type of liquid crystal and the selection of the functional group, or alternatively. As shown in FIG. 2, the mesogenic ligand nanoparticle conjugate including the spacer can achieve improved dispersibility in the liquid crystal compound. The polymer matrix 30 without surface modification of the mesogenic ligand nanoparticle conjugate may increase aggregation and phase separation in the liquid crystal compound, as shown in FIG. 3. As can be seen from FIG. 4, the dispersibility can be further improved with the emulsified liquid crystal compound.
[0041] In some embodiments, the relative amounts of the components can be adjusted to improve the dispersibility of the mesogenic ligand nanoparticle complex in the liquid crystal compound. In some embodiments, the relative molar amount of the mesogenic ligand to the alkylamine spacer can be about 2:1 to about 1:2 (e.g., 1:1). In some embodiments, the relative molar amount of the mesogenic ligand to the alkylthiol spacer can be about 2:1 to about 1:2 (e.g., 1:1).
[0042] In some embodiments, the mesogenic ligand nanoparticle conjugate comprises a nanoparticle. In some embodiments, the nanoparticle is covalently bound to the mesogenic ligand and / or analogues thereof described above. In some embodiments, the nanoparticle may be conductive. In some embodiments, the nanoparticle may comprise a metal. In some embodiments, the nanoparticle may be a precious metal nanoparticle. In some embodiments, the precious metal nanoparticle may comprise gold, silver or platinum nanoparticles, or combinations thereof. In some embodiments, the nanoparticle may comprise a semiconductive material. In some embodiments, the semiconductive material may be indium tin oxide (ITO), zirconium dioxide (ZiO2), titanium dioxide (TiO2), or combinations thereof. In some embodiments, the nanoparticle may comprise a ferroelectric material. In some embodiments, the ferroelectric material may be BaTiO3. In some embodiments, the nanoparticles described above may have an average diameter of about 50 nm to about 70 nm, about 50 nm to 55 nm, about 55 nm to 60 nm, about 60 nm to 65 nm, about 65 nm to 70 nm, or about 60 nm, or any average diameter within a range defined by any of these values. In some embodiments, the nanoparticles are selected for their conductive and ferroelectric properties. In some embodiments, the nanoparticles are selected for their ability to match mesogenic ligands for binding. In some embodiments, -SH is suitable for gold nanoparticles and readily binds to gold nanoparticles, and -NH2 is suitable for indium tin oxide nanoparticles and readily binds to indium tin oxide nanoparticles.
[0043] In some embodiments, the mesogenic ligand nanoparticle conjugates are selected for their ability to improve the dispersibility of inorganic nanoparticles in liquid crystal compositions. Inorganic nanoparticles can be characterized as having the ability to reduce the drive voltage of a device by trapping impurity ions often present in liquid crystal compositions. Increasing the dispersibility of the inorganic nanoparticles can increase the number of impurity ions captured by the inorganic nanoparticles, which can further reduce the drive voltage of the device.
[0044] In some embodiments, the mesogenic ligand nanoparticle conjugate comprises an interactive end group. In some embodiments, the interactive end group is [ka] The interactive end groups allow the ionic groups to react with impurity ions dispersed within the polymer matrix 30, such as inorganic ions present or otherwise produced within the matrix, e.g., Na + , NH4 + , K + , Mg 2+ , Ca 2+ , Zn 2+ , Al 3+ , F - , Cl - , NO3 - , NO2 - , Br - and / or SO4 2- It is believed that this allows the mesogenic ligand nanoparticle conjugate to interact, e.g., absorb and / or bind, with the mesogenic ligand nanoparticle conjugate. In some embodiments, the mesogenic ligand nanoparticle conjugate may comprise a saturated or unsaturated aryl group, e.g., the end group may be a hydrogen group.
[0045] In some embodiments, the weight percent of the mesogenic ligand nanoparticle conjugate is from about 0.001% to about 10% by weight of the total weight of the polymer matrix 30, or from about 0.01% to about 10% by weight, from about 0.1% to about 10% by weight, from about 0.01% to about 1% by weight, from about 1% to about 2% by weight, from about 2% to about 3% by weight, from about 3% to about 4% by weight, from about 4% to about 5% by weight, from about 5% to about 6% by weight, from about It can be in the range of 6% by weight to about 7% by weight, about 7% by weight to about 8% by weight, about 8% by weight to about 9% by weight, about 9% by weight to about 10% by weight, or about 0.001% by weight, about 0.01% by weight, about 0.1% by weight, about 1% by weight, about 2% by weight, about 3% by weight, about 4% by weight, about 5% by weight, about 6% by weight, about 7% by weight, about 8% by weight, about 9% by weight, about 10% by weight, or any weight percentage within a range defined by any of these.
[0046] In some embodiments, the polymer matrix 30 may include at least one liquid crystal compound. The polymer matrix 30 may be prepared by any suitable method. In some embodiments, the polymer matrix 30 may be obtained by mixing and stirring the liquid crystal compound in the dispersed phase with a water-soluble polymer (aqueous phase) or a matrix-forming resin dissolved in water (latex). Details of the preparation of the liquid crystal compound are described, for example, in U.S. Patent Application Publication Nos. 2022 / 0035197, 2021 / 0394504, WO 2021065731, and JP 07019315, the entire contents of which are incorporated herein by reference.
[0047] Some embodiments include a method for producing an emulsion-type PDLC layer (e.g., polymer matrix 30), which includes forming a coating layer by applying an emulsion coating liquid containing a polymer resin and a liquid crystal compound to a transparent electrode layer surface of one of the transparent conductive films, and drying the coating layer to generate a polymer resin matrix on the electrode. In some embodiments, the emulsion coating liquid is preferably an emulsion containing a mixed solution of a polymer resin and a coating solvent in the continuous phase and a liquid crystal compound in the dispersed phase. By applying and drying the emulsified coating liquid, a PDLC layer having a structure in which the liquid crystal compound is dispersed in the resin matrix can be formed. In some examples, the PDLC element is obtained by laminating another transparent conductive film on the PDLC layer.
[0048] Any suitable liquid crystal compound may be used. In some embodiments, at least one liquid crystal compound may comprise a smectic liquid crystal compound. In some embodiments, at least one liquid crystal compound may comprise a cholesteric liquid crystal compound. In some embodiments, at least one liquid crystal compound may comprise a polymer dispersed liquid crystal compound. In some embodiments, the polymer dispersed liquid crystal compound comprises an emulsified polymer dispersed liquid crystal.
[0049] In another embodiment, the at least one liquid crystal compound may include a nematic liquid crystal compound. It is preferable to use a nematic liquid crystal compound because of its excellent transparency characteristics. Examples of nematic liquid crystal compounds include biphenyl compounds, benzoic acid phenyl compounds, cyclohexylbenzene compounds, azoxybenzene compounds, azobenzene compounds, azomethine compounds, terphenyl compounds, benzoic acid biphenyl compounds, cyclohexylbiphenyl compounds, phenylpyridine compounds, cyclohexylpyrimidine compounds, cholesterol compounds, etc.
[0050] In some embodiments, at least one liquid crystal compound may include a resin. Any suitable resin may be used for the liquid crystal compound. For example, polyurethane resin, polyethylene resin, polypropylene resin, polyacrylic resin, etc. may be used. Also, water-soluble polymers such as methacrylate / acrylonitrile copolymer, urethane / acrylate copolymer, or acrylate / acrylonitrile copolymer may be used.
[0051] The total amount of the liquid crystal compound and the resin is preferably about 30 parts by weight to about 70 parts by weight, more preferably about 40 parts by weight to about 60 parts by weight, relative to 100 parts by weight of the polymer matrix 30. Within such a range, a stable emulsion coating liquid can be obtained.
[0052] In some embodiments, the relative weight ratio of the liquid crystal compound to the resin (resin / liquid crystal compound) can be about 10 / 90, about 20 / 80, about 30 / 70, about 40 / 60, about 50 / 50, about 60 / 40, about 70 / 30, about 80 / 20, or about 90 / 10, more preferably about 30 / 70 to about 70 / 30. If the ratio of the liquid crystal compound is too large, it is considered that the liquid crystal emulsion becomes unstable and the droplet size may become coarse over time.
[0053] The liquid crystal compound may further contain a crosslinking agent. When a crosslinking agent is used, the polymer matrix 30 can form a crosslinked structure. Any suitable crosslinking agent can be used as the crosslinking agent. Non-limiting examples of the crosslinking agent include aziridine-based crosslinking agents, isocyanate-based crosslinking agents, and the like. The weight percent of the crosslinking agent can be about 0.5 weight percent to about 10 weight percent, about 0.5 weight percent to 1 weight percent, about 1 weight percent to 5 weight percent, about 5 weight percent to 10 weight percent, about 0.8 weight percent to 5 weight percent, or any weight percent within a range defined by any of these values, relative to 100 parts by weight of the polymer matrix 30.
[0054] The viscosity of the polymer matrix 30 when filling the optical shutter 100 is preferably about 20 mPas to about 400 mPas, more preferably about 30 Pas to 300 mPas, or even more preferably about 40 Pas to 200 mPas. If the viscosity is less than 20 mPas, it is considered that the convection of the solvent (water) becomes large when the solvent dries, and the thickness of the polymer matrix 30 may become unstable. Also, if the viscosity exceeds 400 mPas, it is considered that the beads of the polymer matrix 30 may not be stabilized. The viscosity of the polymer matrix 30 can be measured using a rheometer MCR302 manufactured by Anton Paar. The shear viscosity value of the present disclosure is determined at 20° C., and a shear rate of 1000 per second is used.
[0055] Some examples of liquid crystal compounds that can be used in the present light shutter 100 include, but are not limited to, E7, E8, E44, QY-PDLC8, MLC-2109, MLC-2125, MLC-2132, MLC-2133, MCL-2134, MLC-15600-000, MLC-15600-100, MLC-3003, MLC-3012, and MLC-3016 (Merck KGaA, Germany), NIT1044 (Nitto Denko Corporation), or JM1000XX (Chisso Corporation, Japan). The concentration of at least one liquid crystal compound can be calculated by subtracting the total amount of the chiral dopant(s), reactive mesogenic composition(s), and UV photoinitiator(s) from 100. The weight percent of the at least one liquid crystal compound is about 50% by weight to about 99% by weight of the total weight of the polymer matrix 30, or about 50% by weight to about 55% by weight, about 55% by weight to about 60% by weight, about 60% by weight to about 65% by weight, about 65% by weight to about 70% by weight, about 70% by weight to about 75% by weight, about 75% by weight to about 80% by weight, about 80% by weight to about 85% by weight, about 85% by weight to about 90% by weight, about 90% by weight to about 100% by weight, about 100% by weight to about 15 ... The range can be about 95% by weight, about 95% by weight to about 99% by weight, about 52% by weight, about 53% by weight, about 54% by weight, about 71% by weight, about 72% by weight, about 73% by weight, about 74% by weight, about 82% by weight, about 83% by weight, about 84% by weight, about 85% by weight, about 86% by weight, about 87% by weight, about 88% by weight, or any weight percentage within a range defined by any of these values.
[0056] In some embodiments, the polymer matrix 30 may include a reactive mesogenic composition. In some embodiments, the reactive mesogenic composition may include at least one reactive mesogen. In some embodiments, the reactive mesogenic composition includes at least one polymerizable monomer. In some embodiments, the reactive mesogenic composition may include a photoinitiator. In some embodiments, the at least one reactive mesogenic may be LC242 (BASF, Germany). In some embodiments, the at least one reactive mesogenic may be RM257 (Merck KGaA, Germany). The selection of the reactive mesogenic composition or polymerizable monomer is not particularly limited, and any suitable mesogenic composition or polymerizable monomer may be used.
[0057] In some embodiments, the at least one reactive mesogenic composition may have a concentration ranging from about 0.1% to about 40% by weight of the total weight of the polymer matrix 30. In more preferred embodiments, the at least one reactive mesogenic composition may have a concentration ranging from about 1% to about 35% by weight. In even more preferred embodiments, the at least one reactive mesogenic composition may have a concentration ranging from about 4% to about 15% by weight. At least one reactive mesogenic composition may comprise from about 0.1% to about 1% by weight, from about 1% to about 5% by weight, from about 5% to about 10% by weight, from about 10% to about 15% by weight, from about 15% to about 20% by weight, from about 20% to about 25% by weight, from about 25% to about 30% by weight, from about 30% to about 35% by weight, from about 35% to about 40% by weight, about 1%, about 2%, about 3%, about 4%, about 5%, about 6%, about 7%, about 8%, about 9%, about 10%, about 11%, about 12%, about 13%, about 14%, about 15%, about 16%, about 17%, about 18%, about 19%, about 20%, about 21%, about 22%, about 23%, about 24%, about 25%, about 26%, about 27%, about 28%, about 29%, about 30%, about 31%, about 32%, about 33%, about 34%, about 35%, about 36%, about 37%, about 38%, about 39%, about 40 ... The weight percentage can be 4%, about 15%, about 16%, about 17%, about 18%, about 19%, about 20%, about 21%, about 22%, about 23%, about 24%, about 25%, about 26%, about 27%, about 28%, about 29%, about 30%, about 31%, about 32%, about 33%, about 34%, about 35%, about 36%, about 37%, about 38%, about 39%, about 40%, or any weight percentage within a range defined by any of these values.
[0058] In some embodiments, the polymer matrix 30 of the light shutter 100 may include a photoinitiator. In some embodiments, the photoinitiator may be an ultraviolet (UV) photoinitiator. In some embodiments, the UV photoinitiator may include IrgaCure™ 651 or Irgacure™ TPO (BASF Chemical Co., Ludwigshafen, Germany). The choice of photoinitiator is not limiting, and the photoinitiator may be a UV or thermal activated initiator, etc., and any suitable photoinitiator may be selected depending on the application of the light shutter 100.
[0059] The weight percent of the UV photoinitiator is the weight percent relative to the total weight of the at least one reactive mesogen, such that 1 weight percent is 1% of the total amount of the at least one reactive mesogen (e.g., if the UV photoinitiator is 1 weight percent and the at least one reactive mesogen is 4.7 weight percent, then the UV photoinitiator is 1% of 4.7 weight percent of the total weight of the polymer matrix 30, or 0.047 weight percent). The weight percent of the UV photoinitiator relative to the total weight of the at least one reactive mesogen may range from about 0.035 weight percent to about 5 weight percent, from about 0.03 weight percent to about 4 weight percent, from about 0.035 weight percent to about 3 weight percent, from about 0.4 weight percent to about 2 weight percent, from about 0.5 weight percent to about 1 weight percent, from about 0.1 weight percent, from about 0.15 weight percent, from about 0.2 weight percent, from about 0.25 weight percent, from about 0.3 weight percent, from about 0.35 weight percent, from about 0.4 weight percent, %, about 0.45%, about 0.5%, about 0.55%, about 0.6%, about 0.65%, about 0.7%, about 0.75%, about 0.8%, about 0.85%, about 0.9%, about 0.95%, about 1%, about 2%, about 3%, about 4%, about 5%, or any weight percentage within a range defined by any of these values.
[0060] The optical shutters described herein are useful in methods of controlling the amount of light and / or heat passing through a window. The optical shutters described herein can further be useful in efforts to provide privacy, reduce heat from ambient sunlight, and control the harmful effects of ultraviolet radiation.
[0061] As used herein, and unless otherwise specified, the use of ordinal adjectives such as "first" and "second" to describe a common object merely indicates that different instances of a similar object are being referred to, and is not intended to imply that the objects so described must be in a given order, temporally, spatially, hierarchically, or in any other manner.
[0062] Use of the terms "may" or "may be" shall be construed as shorthand for "is" or "is not," or alternatively, "will" or "will not," or "will not" or "will not." For example, the statement "the thermally conductive composite may further comprise a backing layer" shall be understood as, for example, "in some embodiments, the thermally conductive composite further comprises a backing layer" or "in some embodiments, the thermally conductive composite does not further comprise a backing layer."
[0063] Unless otherwise indicated, any numbers used in the present specification and embodiments expressing properties such as the amount of ingredients, molecular weight, reaction conditions, etc., should be understood to be modified in all cases by the term "about". As used herein, the term "about" can include any numerical value that can vary without changing the basic function of its value. When used in conjunction with a range, "about" also discloses the range defined by the absolute values of the two endpoints. The term "about" can refer to plus or minus 10% of the stated number.
[0064] Accordingly, unless indicated to the contrary, the numerical parameters set forth in the specification and accompanying embodiments are approximations that may vary depending upon the desired properties sought to be obtained, at least not as an attempt to limit the application of the doctrine of equivalents. Within the scope of the embodiments, each numerical parameter should at least be construed in light of the number of reported significant digits and by applying ordinary rounding techniques.
[0065] For the disclosed processes and / or methods, the functions performed in the processes and methods may be realized in various orders, as may be indicated by the context. Moreover, the outlined steps and operations are presented only as examples, and some steps and operations may be optional, combined into fewer steps and operations, or expanded into additional steps and operations.
[0066] This disclosure may at times describe different components contained within or linked to different other components, such depicted structures are merely exemplary, and many other structures may be realized that achieve the same or similar functionality.
[0067] Generally, the terms used in this disclosure and the accompanying embodiments (e.g., the body of the accompanying embodiments) are intended as "open" terms (e.g., the term "including" should be interpreted as "including, but not limited to", the term "having" should be interpreted as "having at least", the term "includes" should be interpreted as "includes, but not limited to", etc.). Furthermore, when a specific number of elements is introduced, this may be interpreted to mean at least the number recited, as may be indicated by the context (e.g., the bare recitation of "two descriptions" without other qualifiers means at least two descriptions of the two or more descriptions). As used in this disclosure, any disjunction and / or disjunction phrase expressing two or more alternative terms should be understood to contemplate the possibility of including one of the terms, either of the terms, or both terms. For example, the phrase "A or B" will be understood to include the possibilities of "A" or "B" or "A and B."
[0068] The terms "a," "an," "the," and similar referents used in the context of describing this disclosure (particularly in the context of the following embodiments) should be construed to include both the singular and the plural, unless otherwise indicated herein or clearly contradicted by context. The use of any and all examples or representative language (e.g., "such as") set forth herein is intended merely to better clarify the disclosure and does not pose a limitation on the scope of any embodiment. Language in this specification should not be construed as indicating any non-embodied element essential to the practice of the disclosure.
[0069] Groupings of alternative elements or embodiments disclosed herein should not be construed as limiting. Each group member may be referenced and embodied individually or in any combination with other members of the group or other elements found herein. It is anticipated that for reasons of convenience and / or patentability, one or more members of a group may be included in or deleted from a group. When such inclusions or deletions are made, the specification is deemed to satisfy the description of all Markush groups used in the appended embodiments, to include the modified group.
[0070] Certain embodiments are described herein, including the best mode known to the inventors for carrying out the present disclosure. Of course, variations of these described embodiments will become apparent to those skilled in the art upon reading the above description. The inventors anticipate that those skilled in the art will use such variations as necessary, and the inventors intend for the present disclosure to be carried out in ways other than as specifically described herein. Thus, the embodiments include all modifications and equivalents of the subject matter described in the embodiments, as permitted by applicable law. Moreover, any combination of the above elements in all possible variations thereof is contemplated, unless otherwise indicated herein or clearly contradicted by context. Finally, it should be understood that the embodiments disclosed herein are illustrative of the principles of the embodiments. Other variations that may be used are within the scope of the embodiments. Thus, by way of example, but not limitation, alternative embodiments may be utilized in accordance with the teachings of the present specification. Thus, the embodiments are not limited to those precisely shown and described.
[0071] Exemplary embodiments and methods are described in more detail below.
[0072] Embodiment Embodiment 1 An optical shutter comprising: a first base material having a transparent electrode layer; a second base material provided with a transparent electrode layer; a polymer matrix comprising at least one mesogenic ligand nanoparticle conjugate and at least one liquid crystal compound, the polymer matrix being disposed between a first base material and a second base material; An optical shutter.
[0073] Embodiment 2 The optical shutter of embodiment 1, wherein the mesogenic ligand nanoparticle conjugate comprises an alkylamine ligand or an arylamine ligand.
[0074] Embodiment 3 A mesogenic ligand nanoparticle conjugate having the general formula: [ka] 3. The optical shutter of embodiment 2, comprising a ligand of the formula: wherein X can be -O- or -S-, n can be from about 5 to about 15, and R is independently selected from -COOH, -C=CH2, -OH, -SH, -NH2 and / or -N3.
[0075] Embodiment 4 The mesogenic ligand nanoparticles have the following structure: [ka] (wherein n can be from about 5 to about 15 and X can be -O- or -S-).
[0076] Embodiment 5. The mesogenic ligand nanoparticle conjugate of the formula: [ka] 2. The optical shutter of embodiment 1, comprising one of the following: wherein R is independently selected from: -COOH, -C=CH2, -OH, -SH, -NH2, and / or -N3, or a combination thereof.
[0077] Embodiment 6. The optical shutter of embodiment 1, wherein the mesogenic ligand nanoparticle conjugate comprises a precious metal nanoparticle.
[0078] Embodiment 7. The optical shutter of embodiment 6, wherein the precious metal nanoparticles comprise gold nanoparticles.
[0079] Embodiment 8. The optical shutter of embodiment 1, wherein the mesogenic ligand nanoparticle complex comprises a semiconducting material.
[0080] Embodiment 9. The optical shutter of embodiment 8, wherein the semiconductive material comprises indium tin oxide.
[0081] Embodiment 10. The optical shutter of embodiment 1, wherein the concentration of the mesogenic ligand nanoparticle conjugate is from about 0.01% to about 5% by weight of the total weight of the polymer matrix.
[0082] Embodiment 11. The optical shutter of embodiment 1, wherein the polymer matrix further comprises an alkylamine spacer or an alkylthiol spacer, and the ratio of alkylamine spacer to mesogenic ligand nanoparticle conjugate, or the ratio of alkylthiol spacer to mesogenic ligand nanoparticle conjugate, is from about 2:1 to about 1:2.
[0083] Embodiment 12 The light shutter of embodiment 1, wherein the at least one liquid crystal compound comprises a polymer dispersed liquid crystal.
[0084] Embodiment 13 The optical shutter of embodiment 1, wherein the at least one liquid crystal compound comprises an emulsified polymer dispersed liquid crystal.
[0085] Embodiment 14 The optical shutter of embodiment 1, wherein at least one liquid crystal compound comprises a resin. EXAMPLES
[0086] It has been found that embodiments of light shutters comprising a polymer matrix as described herein exhibit improved performance compared to other forms of light shutters. These advantages are further demonstrated by the following examples, which are intended only to illustrate the disclosure and are in no way intended to limit the scope or underlying principles.
[0087] Synthesis of mesogenic ligand nanoparticles Various kinds of mesogenic ligands were synthesized and specifically attached to the surfaces of various nanoparticles, where we use thiol-mesogenic ligands for gold nanoparticles and amine-mesogenic ligands for ITO nanoparticles as examples.
[0088] Synthesis of mesogenic ligand (ML-1): [ka]
[0089] 4'-Phenylphenol (1.0 equiv.), 1,12-dibromododecane (3.0 equiv.) and K2CO3 (3.0 equiv.) were placed in a single-neck round-bottom flask with acetone under stirring. The resulting suspension was heated to reflux for more than 20 h and then placed under vacuum. The resulting solid was dispersed in dichloromethane (DCM) and then washed with Di-H2O to remove residual salts. The filtrate was concentrated under reduced pressure and then purified by column chromatography (1:1 dichloromethane-hexane) to give the desired compound 1.
[0090] A 50 mM solution of compound 1 (1.0 equiv.) in absolute ethanol and thiourea (2.3 equiv.) was refluxed for 20 h. After the solution was cooled to room temperature, the solid was filtered and then crystallized from warm ethanol to give the desired compound 2.
[0091] Compound 2 (1.0 equiv., 42 mM) and potassium hydroxide (KOH, 1.3 equiv.) were dispersed in a 1:3 volume to volume mixture of ethanol and water. The reaction mixture was refluxed under argon protection for 7 h. After cooling to room temperature, the mixture was acidified to pH=4 with concentrated acetic acid and stirred for an additional 2 h. The mixture was concentrated under reduced pressure to give a white residue. The residue was partitioned between dichloromethane and water. The organic layer was collected, dried over CaCl2, and then concentrated to give the desired ML-1.
[0092] Water-dispersible gold nanoparticles with 4-(N,N-dimethylamino)pyridine (DMAP) were synthesized for further mesogenic ligand conjugation. Tetrachloroaurate was dissolved in 80 ml water at a concentration of 32 mM. Tetraoctylammonium bromide was dissolved in 200 ml toluene at a concentration of 56 mM under sonication and then added to the previous gold solution with vigorous stirring. After 30 min of reaction, the gold was transferred to the organic phase. Next, 60 ml of aqueous sodium borohydride solution at a concentration of 661 mM was added dropwise to the mixture, which turned violet-brown within a few minutes and was stirred vigorously overnight. The organic layer was separated and washed with water to obtain a purple solution. This purple solution was then diluted to 500 ml with toluene and transferred to a 2 liter funnel. 500 ml of 50 mM aqueous DMAP solution was carefully poured into the funnel. The bottom aqueous layer was removed and diluted to 500 ml and then stored at 4°C for further use. 25 ml of the AuNP aqueous solution was freeze-dried and then weighed, revealing a gold concentration of 0.3 mg / ml.
[0093] The synthesized ML-1 and 1-hexanethiol were dissolved in acetone at a concentration of 0.3 mM, and 50 ml of the DMAP-AuNP solution was added directly to 20 ml of the above solution under vigorous stirring. After overnight, the dark precipitate formed in the reaction mixture was separated by centrifugation (12000 rpm, 10 min, 10°C). The nanoparticles were then redispersed in a minimum amount of dichloromethane, precipitated with chilled ethanol, and then separated by centrifugation (12000 rpm, 10 min, 10°C). This process was repeated four times until the excess mesogenic ligands were removed. The isolated nanoparticles (also referred to as "ML-Au" in the attached figures) were dried and stored at room temperature for further use.
[0094] Synthesis of mesogenic ligand (ML-2): [ka]
[0095] Phthalimide (1.0 equiv.), 1,12-dibromododecane (3.0 equiv.) and K2CO3 (3.0 equiv.) were placed in a single-neck round-bottom flask with acetone under stirring. The resulting suspension was heated to reflux for more than 20 h and then concentrated under vacuum. The resulting solid was dispersed in DCM and then washed with Di-H2O to remove residual salts. The filtrate was concentrated under reduced pressure and then purified by column chromatography (1:3 ethyl acetate-hexane) to give the desired compound 3.
[0096] Compound 3 (1.0 equiv.), 4'-hydroxybiphenyl-4-carbonitrile (2.0 equiv.) and K2CO3 (3.0 equiv.) were dispersed in acetone and refluxed at a temperature of 60°C for more than 20 hours. After concentration under reduced pressure of about -80 kPa to about -90 kPa, the resulting solid was dispersed in DCM and then washed with Di-H2O to remove residual salts. The filtrate was concentrated under reduced pressure of about -80 kPa to about -90 kPa and then purified by column chromatography (1:1 dichloromethane-hexane) to give the desired compound 4.
[0097] A solution of compound 4 (1.0 equiv.) and hydrazine monohydrate (13.0 equiv.) in ethanol was refluxed for 4 h. After cooling to room temperature, the mixture was concentrated under reduced pressure. 5 ml to 10 ml of dichloromethane was added to the residue, which was then filtered to remove undissolved compounds. The clear solution in dichloromethane was concentrated under reduced pressure to give the desired compound ML-2.
[0098] Subsequently, 50 mg / ml of ITO nanoparticles were dispersed in a trimesic acid / ethanol solution (2.1 g in 50 ml) under sonication. The mixture was kept at room temperature for 3 days under gentle stirring. The ITO nanoparticles were then collected by centrifugation (10000 rpm, 10 min) and repeatedly washed with acetonitrile under sonication. Finally, the sample was dried by lyophilization to obtain ITO nanoparticles with carboxyl group modification (COOH-ITO).
[0099] 40 mg of COOH-ITO nanoparticles were dispersed in dichloromethane (5 ml) under sonication. Then, 80 mg of ML-2 was added together with 720 mg of dicyclohexylcarbodiimide and 144 mg of 4-dimethylaminopyridine under stirring. The resulting solution was stirred at room temperature for 3 days to allow coupling. The mixture was then diluted with dichloromethane and centrifuged (10000 rpm, 10 min) to separate the nanoparticles. The nanoparticles were washed multiple times with dichloromethane until excess unreacted chemicals were removed. The mesogenic ligand modified ITO nanoparticles (ML-2-ITO, or ML-ITO) were obtained after freeze-drying.
[0100] Synthesis of mesogenic ligand (ML-8): [ka]
[0101] Phthalimide (1.0 equiv.), 1,12-dibromododecane (3.0 equiv.) and K2CO3 (3.0 equiv.) were placed in a single-neck round-bottom flask with acetone under stirring. The resulting suspension was heated to reflux for more than 20 h and then concentrated under vacuum. The resulting solid was dispersed in DCM and then washed with Di-H2O to remove residual salts. The filtrate was concentrated under reduced pressure and then purified by column chromatography (1:3 ethyl acetate-hexane) to give the desired compound 3.
[0102] Compound 3 (1.0 equiv.), 3,4,5-trifluorophenol (1.5 equiv.) and K2CO3 (3.0 equiv.) were placed in a single-neck round-bottom flask with acetone under stirring. The resulting suspension was heated to reflux for more than 20 h and then concentrated under vacuum. The resulting solid was dispersed in DCM and then washed with Di-H2O to remove residual salts. The filtrate was concentrated under reduced pressure at about -80 kPa to about -90 kPa and then purified by silica gel column chromatography (dichloromethane) to give the desired compound 5.
[0103] A solution of compound 5 (1.0 equiv.) and hydrazine monohydrate (13.0 equiv.) in ethanol was refluxed for 4 h. After cooling to room temperature, the mixture was concentrated under reduced pressure. 5 ml to 10 ml of dichloromethane was added to the residue, which was then filtered to remove undissolved compound. The clear solution in dichloromethane was concentrated under reduced pressure to give the desired compound ML-8.
[0104] 40 mg of COOH-ITO nanoparticles were dispersed in dichloromethane (5 ml) under sonication. Then, 80 mg of ML-8 was added together with 720 mg of dicyclohexylcarbodiimide and 144 mg of 4-dimethylaminopyridine under stirring. The resulting solution was stirred at room temperature for 3 days to allow coupling. The mixture was then diluted with dichloromethane and centrifuged (10000 rpm, 10 min) to separate the nanoparticles. The nanoparticles were washed multiple times with dichloromethane until excess unreacted chemicals were removed. Mesogenic ligand nanoparticles (ML-8-ITO, or FML-ITO) were obtained after freeze-drying.
[0105] Preparation of coatable PDLC formulations 50 parts by weight of water-based aliphatic polyurethane latex (Zeneca, product name "Neorez (trademark) R-967" containing 35% by weight of latex particles) was added to 50 parts by weight of liquid crystal compound (product name "JM1000XX", Chisso Corporation). The mixture was then stirred using an Excel Auto Homogenizer (Nihon Seiki Seisakusho Co., Ltd.) while maintaining the stirring section at 40°C, to obtain liquid crystal compound 1 (emulsified liquid crystal compound). The viscosity of liquid crystal compound 1 was 65 mPas.
[0106] PDLC Light Shutter Manufacturing Preparation process 15 mg of ITO nanoparticles were weighed and added to a 20 ml glass vial. 5 ml of DCM was added to the ITO nanoparticles and sonicated for 5 min, after which a light green dispersion was visually observed. 1 g of liquid crystal compound 1 was added and gently stirred until completely dissolved. The dispersion was then probe sonicated in an ice bath (60% amplitude, 2 sec on, 2 sec off, 8 min) to improve dispersion (parameters can be optimized based on the type of nanoparticles). Next, one stir bar was placed into the mixture and the mixture was stirred at 500 rpm overnight with the lid open to evaporate the solvent. The mixture was then left at room temperature under vacuum for 30 min to 1 h to evaporate all the solvent.
[0107] LC Compound Emulsion The emulsifier stock solution is 10% and is diluted to 1% when used. Take 1 g of LC-NP mixture and place it in a 3 ml syringe. Then, use another 3 ml syringe to collect 1 ml of 1% emulsifier in the syringe. Place a filter in the middle of the two syringes and push and pull them 40 times to obtain emulsified liquid crystal compound 1.
[0108] Fabrication of PDLC devices Using a slot die (lip thickness (width) 3 mm) or a Mayer rod, the emulsified liquid crystal compound 1 is coated (applied and dried) onto the first transparent conductive film. In this way, an emulsified liquid crystal layer having a thickness of 20 μm is formed. Next, a second transparent conductive film is laminated and stacked on the emulsified liquid crystal layer to obtain a light control layer film. In addition, a transparent conductive layer composed of an ITO layer is formed on a PET substrate as the first transparent conductive film and the second transparent conductive film.
[0109] Optical (Haze) Measurements: The optical properties of the optical shutters are characterized by measuring the light passing through each fabricated shutter both in the presence and absence of an electric field. The optical transmittance data of the samples was measured using a haze meter (NDH 7000 from Nippon Denshoku Industries Co., Ltd. (NDK, Japan)) with each sample placed in the device. The light source was measured directly without any sample present to establish a baseline measurement of the total amount of light transmitted. The sample was then placed directly in the light path so that the emitted light would pass through the sample. The sample was then placed in the haze meter while it was connected via wires to a voltage source (3PN117C variable transformer, Superior Electric, Farmington, Connecticut, USA). One wire was connected to each terminal and to each of the ITO glass substrates of the device such that when the voltage source was activated or a voltage was applied, an electric field was applied across the device. The emitted light transmitted through the sample was then measured at different times, first with no voltage applied and then again with voltages of various magnitudes ranging from 0 volts to 60 volts applied in 5 volt increments. 5 to 10 show curves of haze level versus applied voltage in various examples.
Claims
1. An optical shutter, a first base element comprising a transparent electrode layer; a second base element provided with a transparent electrode layer; a polymer matrix comprising a mesogenic ligand nanoparticle conjugate and a liquid crystal compound disposed between the first base element and the second base element; An optical shutter.
2. 10. The optical shutter of claim 1, wherein the mesogenic ligand nanoparticle conjugate comprises an alkylamine ligand or an arylamine ligand.
3. The mesogenic ligand nanoparticle conjugate has the general formula: 【Chemistry 1】 where X can be -O- or -S-, n can be from about 5 to about 15, and R can be -COOH, -C=CH 2 , -OH, -SH, -NH 2 Or -N 3 3. An optical shutter as claimed in claim 1 or 2, comprising a ligand of the formula:
4. The mesogenic ligand nanoparticle conjugate comprises: 【Chemistry 2】 4. The optical shutter of claim 1, comprising: (wherein n can be from about 5 to about 15 and X can be -O- or -S-), or a combination thereof.
5. The mesogenic ligand nanoparticle conjugate comprises: 【Chemistry 3】 (Wherein, R is —COOH, —C═CH 2 , -OH, -SH, -NH 2 Or -N 3 10. The optical shutter of claim 1 , comprising:
6. The optical shutter of claim 1 , wherein the mesogenic ligand nanoparticle conjugate comprises a noble metal nanoparticle.
7. The optical shutter of claim 6 , wherein the noble metal nanoparticles comprise gold (Au) nanoparticles.
8. The optical shutter of claim 1 , wherein the mesogenic ligand nanoparticle conjugate comprises a semiconducting material.
9. The optical shutter of claim 8 , wherein the semiconductive material comprises indium tin oxide (ITO) nanoparticles.
10. 2. The optical shutter of claim 1, wherein the concentration of said mesogenic ligand nanoparticle conjugate is from about 0.01% to about 5% by weight of the total weight of said polymer matrix.
11. The optical shutter of claim 1 , wherein the polymer matrix further comprises a spacer compound.
12. 12. The optical shutter of claim 11, wherein the spacer compound comprises an alkylamine spacer or an alkylthiol spacer, and the relative amount of the alkylamine spacer to the mesogenic ligand nanoparticle conjugate, or the relative amount of the alkylthiol spacer to the mesogenic ligand nanoparticle conjugate, is from about 2:1 to about 1:
2.
13. The optical shutter of claim 1 , wherein the liquid crystal compound comprises a polymer dispersed liquid crystal.
14. 10. The optical shutter of claim 1, wherein the liquid crystal compound comprises an emulsified polymer dispersed liquid crystal.
15. The optical shutter of claim 1 , wherein the liquid crystal compound comprises a resin.